Structure analysis of human gut microbiota associated with single-celled gut protists using Next-Generation Sequencing of 16S and 18S rRNA genes - Salem Belkessa; Edoardo Pasolli; Bachir Medrouh; Rebecca P.K.D. Berg; Lee O.’Brien Andersen; Henrik Vedel Nielsen; Christen Rune Stensvold (Computational and Structural Biotechnology Journal)
The gut microbiota is a complex microbial ecosystem with a major impact on health and disease. Some gut unicellular eukaryotes (particularly Blastocystis) have been linked to features of intestinal eubiosis. Meanwhile, little is known regarding associations between gut-pathogenic protozoa, such as Giardia, and gut microbiota signatures. We therefore characterized and compared gut microbiota profiles of 60 Giardia-positive and 31 Giardia-negative Algerian individuals using amplicon-based next-generation sequencing of prokaryotic and eukaryotic ribosomal genes and stratifying for co-colonization with other unicellular eukaryotes, such as species of Archamoebae or Blastocystis. Overall, we found that alpha and beta microbiota diversity did not differ significantly between Giardia-positive and Giardia-negative individuals, regardless of the presence or absence of Archamoebae and Entamoeba (p > 0.05). However, significant differences were observed in both alpha and beta diversity between Giardia-positive, Blastocystis-negative and Giardia-positive, Blastocystis-positive individuals (observed richness, p = 0.0016; ANOSIM = 0.001), and similar differences were noticed between Blastocystis-negative and-positive carriers (p < 0.05), regardless of Giardia carrier status. Importantly, these differences in gut microbiota were considered to be independent of factors such as sex, age, and location (p > 0.05). Conclusively, Giardia-positive individuals may exhibit features of eubiosis, but whether this depends on the presence of Blastocystis should be confirmed by future studies. These findings combined might indicate that Blastocystis could be an active driver of gut microbiota diversity.